Mapping Democracy on Government and Governance in ASEAN Members - Yusep Ginanjar; Putri Auliya (Journal Of Global Strategic Studies, 2024)
To analyzes Southeast Asia's governance systems and makes policy recommendations to enhance practices in the domain of governance The paper discusses the governance and growth nexus in Southeast Asia; describes the operating governance systems in Southeast Asia; examines economic governance, specifically in the areas of economic management and growth, revenue generation, social spending, access to services, cost of doing business, and corporate governance; and examines political governance, with a focus on the rule of law and judicial systems. To maintain the pace for broad-based prosperity, Southeast Asian nations must build and improve transparency and accountability systems in both the public and private sectors, regardless of degree of development. They must also increase the budgetary sovereignty of their subnational divisions and provide greater opportunity for civil society engagement. Strong law enforcement procedures, as well as more responsive and streamlined regulatory frameworks, are required. For data collection methods use descriptive analysis, which is based on literature studies. This literature study itself is sourced from several journals and books related to the government system of ASEAN countries. To analyzes Southeast Asia's governance systems and makes policy recommendations to enhance practices in the domain of governance The paper discusses the governance and growth nexus in Southeast Asia; describes the operating governance systems in Southeast Asia; examines economic governance, specifically in the areas of economic management and growth, revenue generation, social spending, access to services, cost of doing business, and corporate governance; and examines political governance, with a focus on the rule of law and judicial systems. To maintain the pace for broad-based prosperity, Southeast Asian nations must build and improve transparency and accountability systems in both the public and private sectors, regardless of degree of development. They must also increase the budgetary sovereignty of their subnational divisions and provide greater opportunity for civil society engagement. Strong law enforcement procedures, as well as more responsive and streamlined regulatory frameworks, are required. For data collection methods use descriptive analysis, which is based on literature studies. This literature study itself is sourced from several journals and books related to the government system of ASEAN countries.